Impact of drug supply chain on the dynamics of infectious diseases. (8th July 2018) - Paul, Siddhartha; Venkateswaran, Jayendran
Abstract: The effect of drug shortages on estimating the infectivity of antiviral‐treatable disease epidemics is evaluated using an illustrative dataset. Simulation‐based analysis shows that a given outbreak can be caused by either (i) a high infectivity parameter even with sufficient and timely supply of medicines, or (ii) a low infectivity parameter and poor supply of medicines. Also, the use of a stand‐alone epidemic model is found to overestimate disease transmissibility. A compartmental epidemic model is integrated with multi‐echelon supply chain models to further investigate the impact of medicine supply chain on the epidemic dynamics. In integrated models, medicine demands for the supply chain are generated from the disease model, and the medicine supply rate controls the recovery rate of patients in the disease model. It is found that supply chain aspects have a significant effect on epidemic dynamics. Some improvement schemes for supply chain management are also highlighted.